2017
DOI: 10.1136/bmjopen-2016-014215
|View full text |Cite
|
Sign up to set email alerts
|

Association between soil heavy metals and fatty liver disease in men in Taiwan: a cross sectional study

Abstract: ObjectivesMetabolic factors are major risk factors for non-alcoholic fatty liver disease although other factors may also contribute to development of fatty liver disease. We explored the association between exposure to soil heavy metals and prevalence of fatty liver disease.MethodsWe retrospectively analysed data from patients diagnosed with fatty liver disease in 2014 at the Health Evaluation Centre of Chang-Hua Christian Hospital (n=1137). We used residency data provided in the records of the Health Evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 39 publications
1
16
0
3
Order By: Relevance
“…Nos demais estudos, a quantificação da exposição se deu pela análise de urina (n=5) (16,17,(19)(20)(21) , sangue (n=3) (22)(23)(24) , ou ambos (n=2) (25,26) , ou análise do solo (n=1) (27) Os estudos abrangeram diversos desreguladores endócrinos, com destaque ao Bisfenol A (BPA) (16,17,26) e ao Trialometanos (THM) (20,24) . Arsênico (19) , cádmio (21) , ferro (22) , metais pesados (27) , produtos petroquímicos (18) , chumbo, mercúrio e bifenilos policlorados (PCB) (25) e éter butílico metil terciário (MTBE) (23) também foram avaliados. Artigos que avaliaram a exposição à sobrecarga de ferro (22) e ao MTBE (23) A DHGNA é reconhecida como a doença hepática mais comum em países ocidentais, alcançando proporções epidêmicas nas últimas duas décadas (28,29) .…”
Section: Métodosunclassified
See 2 more Smart Citations
“…Nos demais estudos, a quantificação da exposição se deu pela análise de urina (n=5) (16,17,(19)(20)(21) , sangue (n=3) (22)(23)(24) , ou ambos (n=2) (25,26) , ou análise do solo (n=1) (27) Os estudos abrangeram diversos desreguladores endócrinos, com destaque ao Bisfenol A (BPA) (16,17,26) e ao Trialometanos (THM) (20,24) . Arsênico (19) , cádmio (21) , ferro (22) , metais pesados (27) , produtos petroquímicos (18) , chumbo, mercúrio e bifenilos policlorados (PCB) (25) e éter butílico metil terciário (MTBE) (23) também foram avaliados. Artigos que avaliaram a exposição à sobrecarga de ferro (22) e ao MTBE (23) A DHGNA é reconhecida como a doença hepática mais comum em países ocidentais, alcançando proporções epidêmicas nas últimas duas décadas (28,29) .…”
Section: Métodosunclassified
“…Vale ressaltar que a exposição a determinadas substâncias químicas, conhecidas como DE, pode provocar a progressão da DHGNA para suas formas mais graves de esteatohepatite e cirrose (21,26,27) . Na população obesa, a chance de desenvolver DHGNA mediante a maior exposição a DE é 50% maior (25) .…”
Section: Métodosunclassified
See 1 more Smart Citation
“…The genetic variant, PNPLA3, which is common among Hispanics, has been associated with alanine aminotransferase (ALT) levels, a marker of liver damage, and increased hepatic fat [ 5 7 ]. Recent evidence suggests that exposure to environmental pollutants including those that are inhalation and ingestion toxicants [ 8 10 ], including heavy metals such as arsenic [ 11 ], may play a role. Lin et al previously found a significant association between several soil-derived heavy metals, including arsenic, and NAFLD in lean Tiawanese men, but the independent effect of arsenic was not examined [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic disorders are major risk factors for NAFLD, although other factors may also contribute to development of fatty liver disease. Lin (Lin et al, 2017) suggests a significant association between exposure to soil heavy metals and fatty liver disease in lean men. Besides environmental Cd exposure has been associated with hepatic necroinflammation, NAFLD and NASH in men .…”
Section: Conclusiónmentioning
confidence: 99%